A theoretical model for the buckling characteristics of a laminated composite cylindrical shell with circular cutouts. (3rd September 2022) - Kim, Yongha; Park, Jungsun
Abstract : In this article, the effective stiffness of a laminated composite cylinder with circular cutouts is defined by the homogenization method. Based on the continuous model, a simplified theory is presented for conducting the buckling analysis of the laminated composite cylinder with circular cutouts. The simplified theory is defined by the Ritz method. By the finite element analysis and experimental analysis, the validity of the simplified theory is verified. Finally, the simplified theory is applied to optimize a laminated composite cylinder with circular cutouts for an aerospace application to minimize mass. The optimization result allows a database to be calculated on the buckling characteristics of laminated composite cylinders with circular cutouts for aerospace applications. Consequently, it is concluded that the simplified theory is well suited to the buckling analysis of a laminated cylindrical structure with circular cutouts in aerospace applications due to their simplicity and computational efficiency.